Association of low dietary folate intake with lower CAMKK2 gene methylation, adiposity, and insulin resistance in obese subjects - Ramos-Lopez, Omar; Samblas, Mirian; Milagro, Fermin I.; Zulet, M. Angeles; Mansego, Maria L.; Riezu-Boj, Jose I.; Martinez, J. Alfredo (Nutrition research (New York, N.Y.), 2018)
Folate deficiency has been putatively implicated in the onset of diverse metabolic abnormalities, including insulin resistance, by altering epigenetic processes on key regulatory genes. The calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK2) is involved in the regulation of critical metabolic processes such as adiposity and glucose homeostasis. This study hypothesized associations between low folate intakes and lower methylation levels of the CAMKK2 gene, with the presence of metabolic alterations in subjects with obesity. A cross-sectional ancillary study was conducted in obese subjects (n=47) from the RESMENA study (Spain). Fat mass was measured by dual-energy x-ray absorptiometry. Dietary intake and metabolic profile were assessed by validated methods. DNA methylation and gene expression in peripheral white blood cells were analyzed by microarray approaches. A total of 51 cytosine-phosphate-guanine sites were associated with folate intake (false discovery rate values < 0.0001), including one located in the 5′ untranslated region of the CAMKK2 gene (Illumina ID, cg16942632), which was selected and separately analyzed. Subjects with total folate intake lower than 300μg/d showed more fat mass (especially trunk fat), as well as statistically higher levels of glucose, insulin, homeostatic model assessment–insulin resistance (HOMA-IR) index, cortisol, and plasminogen activator inhibitor-1 than those consuming at least or more than 300μg/d. Of note, folate deficiency was related to lower CAMKK2 methylation. Interestingly, CAMKK2 methylation negatively correlated with the HOMA-IR index. Furthermore, CAMKK2 expression directly correlated with HOMA-IR values. In summary, this study suggests associations between low folate intakes, lower CAMKK2 gene methylation, and insulin resistance in obese individuals.